A cultura dos cordéis: território (s) de tessitura de Saberes. - Araujo, Patricia Cristina de Aragao (2007)
This study has as its main concern to understand the educational dimension of the string literature (cordel) pamphlets woven in our daily life and in the popular culture. The "cordel", empiric object of our research, is approached as a learning content, proving to be an important didactic-pedagogic resource to be used in the classroom environment for school disciplines. The guiding thesis of the study is that the educational content which permeates the "cordeis" allows the construction of conceptions on the Northeast (region of Brazil), the dialogue of knowledges and of perceptions concerning its daily life and its culture. The premise from which we proceed is the assumption that the sting literature poet is an educator, whose pedagogic practice is expressed through the cordeis, which are built from the cultural and daily experiences, from conceptions of the human being, and from the social reality that they represent and elaborate in the pamphlets. From the theoretical-methodological point of view, this work is based on the ethnomethodological approach, whose investigative perspective is anchored in the indiciary and ethnografic methods which were used as referential for the composition of the theoretical picture building of the works developed by Michel of Certeau, Alain Coulon, Stuart Hall, Carlo Guinzburg, Raul Fornet-Betancourt and Paulo Freire. As thematic inputs, we used the interculturality, the daily life, the culture, the popular culture, the popular knowledge, the Northeast of Brazil, the territory, the identity and the dialogue, as axes for the understanding of the study object. Besides the cordel and the regional romances used as corpus, we fell back upon the interviews with cordelistas (cordel poets) and other regional romances, that consisted another research source. The results allowed us to conclude that the cordel is a form of production of knowledge, whose pedagogic proposal is woven in the daily life by the poet that composes it, enriching the educational process, because it makes the interaction of multiples knowledges possible and presents important issues that should be inserted in the programmatic content of the subjects that should be worked with the learning community.